Withanolide glucosides from the Rhizomes of Tacca chantrieri - Quynh Chi, Vu Thi; Yen, Pham Hai; Dung, Duong Thi; Nhiem, Nguyen Xuan; Tuan Anh, Hoang Le; Thuy Hang, Dan Thi; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
By various chromatographic separations, three withanolide glucosides, chantriolides A-C were isolated from the rhizomes of Tacca chantrieri. Their structures were elucidated by 1D-, 2D-NMR, and MS spectra and in comparison with the reported data